Impact of the New Financial Services Law in Bolivia on Financial Stability and Inclusion - Heng, Dyna. (Washington, D.C. : International Monetary Fund, 2015)
This paper examines the impact of the new financial services law in Bolivia-including credit quotas and interest rate caps-on financial stability and inclusion. So far, credit to 'targeted' sectors is growing as intended by the law but the increase in the average loan size of microfinance institutions and the declining number of borrowers point to potentially adverse effects of the interest rate caps on financial inclusion. Looking ahead, while the new law contains many good provisions, international experience suggests that promoting financial access through credit quota and interet rate caps is very challenging. Indeed, trying to meet the 2018 credit target for the productive sectors and social housing could imply the build up of significant financial stability risks. These will need careful monitoring and possible modifications to the credit quotas and interest rate caps.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet